Indium-Free PTB7/PC71BM Polymer Solar Cells with Solution-Processed Al:ZnO Electrodes on PET Substrates - P. Fuchs; A. Paracchino; H. Hagendorfer; L. Kranz; T. Geiger; Y. E. Romanyuk; A. N. Tiwari; F. Nüesch (International Journal of Photoenergy)
Inverted PTB7/PC71BM polymer solar cells are prepared on solution-processed Al:ZnO transparent contacts on PET substrates. Al:ZnO is deposited by a low temperature chemical bath deposition route (T < 100°C at any step) to comply with the temperature sensitive substrate. A maximum conversion efficiency of 6.4% and 6.9% is achieved for the indium-free solar cells on PET and glass substrates, respectively. The devices are relatively stable in air whereby an initial efficiency loss in the order of 15% after storage for 15 days can be fully recovered by light soaking.